2006
DOI: 10.1007/s00213-006-0424-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of amygdaloid nuclei in the anxiolytic- and antidepressant-like effects of the V1b receptor antagonist, SSR149415, in rats

Abstract: Microinjection of SSR149415 into the BlA (1-10 ng), but not into the CeA or the MeA, increased the percentage of time spent in the open arms of the elevated plus-maze, indicating anxiolytic-like effects. Furthermore, in the forced-swimming test, microinjection of the drug into the CeA (1, 10, and 100 ng), BlA (1-10 ng), or MeA (100 ng) decreased immobility, an effect which is indicative of an antidepressant-like action. Together, these findings indicate that while the antidepressant-like effects of SSR149415 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 49 publications
3
53
0
Order By: Relevance
“…The present study confirms not only that blocked/absent AVP-signaling within this brain area causes a more active behavioral response during forced swimming, they also extend the previous findings by suggesting that the MeA and, perhaps to a lesser extent the CeA and BLA, plays an important role in the behavioral regulation during defined stressor exposure. Different studies suggested an involvement of amygdaloid V1b receptor in FS behavior (Salome et al, 2006) and V1a receptors in the amygdala, but not in the lateral septum, modulated the behavior in a paradigm for female anxiety (Poirier et al, 2013). In this context it is of note that V1a (Bielsky et al, 2004) and V1b (Egashira et al, 2005) receptor deficient mice failed to show a behavioral difference to WT animals in the FS test.…”
Section: Discussionmentioning
confidence: 90%
“…The present study confirms not only that blocked/absent AVP-signaling within this brain area causes a more active behavioral response during forced swimming, they also extend the previous findings by suggesting that the MeA and, perhaps to a lesser extent the CeA and BLA, plays an important role in the behavioral regulation during defined stressor exposure. Different studies suggested an involvement of amygdaloid V1b receptor in FS behavior (Salome et al, 2006) and V1a receptors in the amygdala, but not in the lateral septum, modulated the behavior in a paradigm for female anxiety (Poirier et al, 2013). In this context it is of note that V1a (Bielsky et al, 2004) and V1b (Egashira et al, 2005) receptor deficient mice failed to show a behavioral difference to WT animals in the FS test.…”
Section: Discussionmentioning
confidence: 90%
“…SSR149415 has no anxiolytic effects in either punished drinking behavior or exploration of the EPM when administered into the LS (Stemmelin et al, 2005). However, infusion of SSR149415 into the basolateral amygdala, but not central or medial nuclei, produces anxiolytic-like effects in performance on the EPM (Salome et al, 2006). All three nuclei contain Avpr1b receptors (Stemmelin et al, 2005) and likely mediate anxiety-related behaviors in both non-humans (Menard and Treit, 1999) and humans (Sheline et al, 1998).…”
Section: Anxiety-high Densities Of Vasopressinergic Fibers (Dementioning
confidence: 97%
“…The forced swim test induces both depression associated behavior and elevated AVP in the SON and PVN [157,158]. V1a antagonist treatment to both the mediolateral septum and amygdala has antidepressant like effects in male animals [159,160], and similar effects are documented following V1b receptor antagonist treatment [148,161]. For male animals, there is evidence to support the hypothesis that depression and anxiety related behaviors are associated with elevated AVP activity in both brain and plasma.…”
Section: Avp and Male Animal Models Of Depression And Anxietymentioning
confidence: 88%